Monofins: A serious training tool - Morales, P. (Swimming Technique, 1998)
Over the last several years, the monofin has appeared with increasing regularity at swim practices throughout the world. Monofinning is actually much more than just an amusing diversion. The monofin is now recognized as a serious training tool by a growing list of accomplished and innovative swim coaches. The article explains - Five Steps to Monofin Technique - How to Train Core Muscles and Improve Efficiency - Training Tips and Suggested Sets - General as well as specific Drills and - Suggested Sets